5 Metalworking and Ritualization: Negotiating Change through Improvisational Practice in Banda, Ghana. Issue 1 (September 2015) - Stahl, Ann B.; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT Villagers of the 15th through mid–16th centuries C.E. in the Banda area of west central Ghana were living in times of change. The Saharan exchange networks that for several centuries had shaped the lives of earlier villagers were to give way by the late 17th century to Atlantic ones. Both offered opportunities (of access to desired goods) and perils (of enslavement). This paper focuses on a metallurgical workshop and the varied ritual practice associated with metalworking as gleaned from residues of stratified depositional practice. A variety of ritualized contexts and object configurations created a scaffolding "meshwork" that animated metallurgical practice, one that was improvised in relation to the broader context of opportunities and perils within which skilled artisans worked. These ritualized configurations were central to how craftsmen calibrated their practice in relation to the shifting global connections and moral terrains of their times.